2012
DOI: 10.1002/qua.24147
|View full text |Cite
|
Sign up to set email alerts
|

ONIOM study of dissociated hydrogen and water on ZnO surface

Abstract: ONIOM calculations using CCSD theory have been performed to study the dissociation of hydrogen and water molecules on ZnO surface. Three different cluster models were used to study the influence of ONIOM layer size at the interaction energies and optimized geometries. The geometric results indicate a near tetrahedral geometry for the interaction of zinc and oxygen sites of dissociated water. The interaction energies are larger for the water dissociation. The ONIOM layer size has more influence on the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…An HF study using a (ZnO) 6 cluster indicated that H 2 dissociation took place on both the Zn and O sites, with a preference on the two-coordinated O sites . A recent reactive molecular dynamics (RMD) simulation of water dissociation on stepped ZnO surfaces shows that the surface H 2 O molecules can dissociate into surface hydroxyls, in agreement with previous reports. , …”
Section: Introductionsupporting
confidence: 88%
“…An HF study using a (ZnO) 6 cluster indicated that H 2 dissociation took place on both the Zn and O sites, with a preference on the two-coordinated O sites . A recent reactive molecular dynamics (RMD) simulation of water dissociation on stepped ZnO surfaces shows that the surface H 2 O molecules can dissociate into surface hydroxyls, in agreement with previous reports. , …”
Section: Introductionsupporting
confidence: 88%
“…61,106 The rest of adsorption conformations lay 20 kJ mol -1 or higher in energy. As happened when dissociating H 2 , the surface atoms recover a near-tetrahedral geometry, 100 in which ZnO surface units elongate their bonds by 18.7 pm, and surface rumpling essentially vanishes.…”
Section: Full Analysis Of H/oh/h 2 O Species On Polar and Nonpolar Surfacesmentioning
confidence: 99%
“…99 When having both species, the overall adsorption strength is enhanced, due to the bulk near-tetrahedral coordination geometry recovery. 100 The simulated IR spectra shown in Figure 3 displays two peaks at 1797 and 3601 cm -1 belonging to surface Zn-H or O s -H stretching vibrations, respectively. These would correspond to the observed peaks by Wang et al at 1613 and 3670 cm -1 , respectively.…”
Section: Indeed Previous Experiments Combining Leed and He-atom Scattering (Has) Experimentsmentioning
confidence: 99%
“…Wander and Harisson used B3LYP hybrid functional calculations to study the geometry and electronic structure of (only) the heterolytically terminated 2 ML-both configuration. Martins et al used high-level CCSD calculations to compare the energetics of the 2 ML-both and molecular H 2 adsorption configurations on small ZnO cluster models.…”
Section: Introductionmentioning
confidence: 99%